The Covenant-Defeasance Option in Corporate Bonds - Bienz, Carsten; Fluck, Zsuzsanna; Thorburn, Karin S (Review of Financial Studies, 2026)
Abstract Corporate bonds include restrictive covenants that may prevent firms from pursuing valuable growth opportunities ex post and are virtually impossible to renegotiate. We study a common but little-known contractual provision—the defeasance option—which allows issuers to immediately remove all covenants without retiring the bond. Our theoretical model predicts, and our empirical analysis confirms, that defeasance inclusion is more likely when covenants are numerous and issuers face financial constraints, uncertainty, and growth opportunities. We also show that investors require lower yields when defeasance is included in noncallable bonds, and higher yields in fixed-price callable bonds, where it raises call risk.